2021
DOI: 10.48550/arxiv.2101.10836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Separating Adaptive Streaming from Oblivious Streaming

Haim Kaplan,
Yishay Mansour,
Kobbi Nissim
et al.

Abstract: We present a streaming problem for which every adversarially-robust streaming algorithm must use polynomial space, while there exists a classical (oblivious) streaming algorithm that uses only polylogarithmic space. This results in a strong separation between oblivious and adversarially-robust streaming algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Naor and Yogev [32] showed that Bloom filters are susceptible to attacks by an adversarial stream of queries. Kaplan et al [25] constructed a streaming problem naturally inspired by the adaptive data analysis literature, which exhibits a large separation between the space complexities in the adversarial and oblivious regimes. On the positive side, several recent works [4,23,48] present generic compilers that transform non-robust randomized streaming algorithms into efficient adversarially robust ones, for various classical problems such as distinct elements counting and 𝐹 𝑝 -sampling, among others.…”
Section: Streaming Algorithmsmentioning
confidence: 99%
“…Naor and Yogev [32] showed that Bloom filters are susceptible to attacks by an adversarial stream of queries. Kaplan et al [25] constructed a streaming problem naturally inspired by the adaptive data analysis literature, which exhibits a large separation between the space complexities in the adversarial and oblivious regimes. On the positive side, several recent works [4,23,48] present generic compilers that transform non-robust randomized streaming algorithms into efficient adversarially robust ones, for various classical problems such as distinct elements counting and 𝐹 𝑝 -sampling, among others.…”
Section: Streaming Algorithmsmentioning
confidence: 99%
“…Naor and Yogev [32] showed that Bloom filters are susceptible to attacks by an adversarial stream of queries. Kaplan et al [25] constructed a streaming problem naturally inspired by the adaptive data analysis literature, which exhibits a large separation between the space complexities in the adversarial and oblivious regimes. On the positive side, several recent works [4,23,48] present generic compilers that transform non-robust randomized streaming algorithms into efficient adversarially robust ones, for various classical problems such as distinct elements counting and 𝐹 𝑝 -sampling, among others.…”
Section: Streaming Algorithmsmentioning
confidence: 99%
“…They showed it for the task of approximating L P norms but their technique stands for other tasks as well. In a recent result, Kaplan, Mansour, Nissim and Stemmer [20] showed a problem that requires polylogarithmic amount of memory in the static case but any adversarially robust algorithm for it requires exponentially larger memory.…”
Section: Related Workmentioning
confidence: 99%